LARANGAN DAN SYARAT MENIKAH PADA MASYARAKAT ADAT MELAYU SAMBAS DI DESA KAUM KECAMATAN SAMBAS - DIZA FADHLA NADHIFAH NIM. A1011181239 (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstrac Tradition has become a unity in society, Tradition is a cultural idea that consists of cultural values, norms, habits, institutions, and customary law that regulate human behavior between one another which is commonly practiced in a community group. Marriage is one of the most important events in social life, because marriage does not only concern women and men who will caress, but also the parents of both parties, their siblings, and even their respective families. Even in customary law, marriage is not only an important event for those who are still alive, but marriage is also a very meaningful event and which is fully paid attention and followed by the spirits of the ancestors of both parties. So from the two differences, there is a prohibition on marriage between the indigenous Malay community of Sambas and the indigenous certain community. So the authors took this research with the title Prohibition and Requirements for Marriage in the Sambas Malay Indigenous Community in the Village of the Sambas District.The formulation of the problem in this research is: